Zeolites featuring 14 × 12-ring channels with unique adsorption properties. Issue 24 (4th November 2021) - Li, Shiqing; Han, Lu; Zhao, Zhonglin; Xu, Hao; Jiang, Jingang; Wu, Peng
Abstract : The lamellar precursor PREFER was applied to develop interlayer expanded zeolite IEZ-FER(D4h) by molecular alkoxysilylation with the assistance of the thermal acid treatment 1, 3, 5, 7-tetramethyl cyclotetrasiloxane (D4h) as the silylating agent to connect neighboring layers. Abstract : The lamellar precursor of the FER type zeolite (PREFER) was applied to develop the interlayer expanded zeolite IEZ (interlayer-expanded zeolite)-FER (D4h) with extra-large pores through hydrothermal acid treatment-assisted molecular alkoxysilylation, using 1, 3, 5, 7-tetramethyl cyclotetrasiloxane (D4h) as a silylating agent to interconnect neighboring zeolitic layers. The interlayer expanded structure was well preserved after calcination at 823 K, yielding a hydrophilic material denoted as IEZ-FER(D4h-B). The as-made IEZ-FER(D4h) exhibits expanded interlayer spacing along the a -axis. The 4-membered rings (4MR) exist in IEZ-FER(D4h) as the secondary structure building units, while the methyl groups therein attached result in the hydrophobic properties. The newly formed channel systems are composed of intersecting 14MR and 12MR pores along the [001] and [010] directions, respectively, which are larger than those of the conventional 3D FER. The powder XRD patterns determine that IEZ-FER(D4h) has a crystalline structure with the IMM2 space group and unit cell parameters of a = 28.0285(39) Å, b = 14.0921(6) Å, c = 7.4395(3) Å.